Cytomegalovirus-Associated Gianotti-Crosti Syndrome in 28-Year-Old Immunocompetent Patient - Florence Dupont; Aurélien Aubry; Jean-Philippe Lanoix; Baptiste Demey (Pathogens, 2022)
Gianotti-Crosti syndrome is a cutaneous eruption that occurs rarely in adults. It mostly concerns pediatric population and immunocompromised patients. Cytomegalovirus has already been described as one etiology of Gianotti-Crosti acrodermatitis in children and bone-marrow transplanted patients. Here, we present a Cytomegalovirus-associated Gianotti-Crosti syndrome in a 28-year-old immunocompetent female patient diagnosed in CHU Amiens-Picardie (Amiens, France). This type of case has never been shared in literature before. This rare complication of Cytomegalovirus infection indirectly led to disruption of anticoagulant treatment and thromboembolic incident that could have been fatal.